The developmental origin of cancers defines basic principles of cisplatin resistance. (28th October 2021) - Skowron, Margaretha A.; Oing, Christoph; Bremmer, Felix; Ströbel, Philipp; Murray, Matthew J.; Coleman, Nicholas; Amatruda, James F.; Honecker, Friedemann; Bokemeyer, Carsten; Albers, Peter; Nettersheim, Daniel
Abstract: Cisplatin-based chemotherapy has been used for more than four decades as a standard therapeutic option in several tumor entities. However, being a multifaceted and heterogeneous phenomenon, inherent or acquired resistance to cisplatin remains a major obstacle during the treatment of several solid malignancies and inevitably results in disease progression. Hence, we felt there was an urgent need to evaluate common mechanisms between multifarious cancer entities to identify patient-specific therapeutic strategies. We found joint molecular and (epi)genetic resistance mechanisms and specific cisplatin-induced mutational signatures that depended on the developmental origin (endo-, meso-, ectoderm) of the tumor tissue. Based on the findings of thirteen tumor entities, we identified three resistance groups, where Group 1 (endodermal origin) prominently indicates NRF2-pathway activation, Group 2 (mesodermal origin, primordial germ cells) shares elevated DNA repair mechanisms and decreased apoptosis induction, and Group 3 (ectodermal and paraxial mesodermal origin) commonly presents deregulated apoptosis induction and alternating pathways as the main cisplatin-induced resistance mechanisms. This review further proposes potential and novel therapeutic strategies to improve the outcome of cisplatin-based chemotherapy. Highlights: Cisplatin induces specific mutational signatures (C > T and C > A) in human cancers . Developmental origin of tumor cells correlates to cisplatin resistance mechanisms. Tumors of endodermal origin indicate NRF2-pathway activation. Elevated DNA repair in tumors derived from the mesoderm and primordial germ cells. Alternating pathways induced in tumors of ectodermal and paraxial mesodermal origin.